2021
DOI: 10.1159/000517615
|View full text |Cite
|
Sign up to set email alerts
|

Nephrologist Interventions to Avoid Kidney Replacement Therapy in Acute Kidney Injury

Abstract: <b><i>Background:</i></b> Based on the pathophysiology of acute kidney injury (AKI), it is plausible that certain early interventions by the nephrologist could influence its trajectory. In this study, we investigated the impact of 5 early nephrology interventions on starting kidney replacement therapy (KRT), AKI progression, and death. <b><i>Methods:</i></b> In a prospective cohort at the Hospital Civil of Guadalajara, we followed up for 10 days AKI patients in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our group showed that uid adjustment was associated with a 42% risk reduction in initiation of KRT (37); it could be that, through this uid adjustment, sK + can decrease and thus improve the clinical course of these patients. In this line, utilization of balanced solutions with physiological concentrations of chloride (Ringer's lactate and Plasmalyte) prevents the development of metabolic acidosis and is associated with lower sK + levels compared to NaCl 0.9% (38).…”
Section: Discussionmentioning
confidence: 84%
“…Our group showed that uid adjustment was associated with a 42% risk reduction in initiation of KRT (37); it could be that, through this uid adjustment, sK + can decrease and thus improve the clinical course of these patients. In this line, utilization of balanced solutions with physiological concentrations of chloride (Ringer's lactate and Plasmalyte) prevents the development of metabolic acidosis and is associated with lower sK + levels compared to NaCl 0.9% (38).…”
Section: Discussionmentioning
confidence: 84%
“…In high-risk patients for AKI, the doses of nephrotoxic drugs and other drugs should be strictly controlled [ 12 ]. Recently, an observational and retrospective study [ 41 ] analyzed 5 interventions of the nephrology team with the potential to meliorate AKI outcomes, including the fluid adjustment and nephrotoxic withdrawal, etc. It reported that only fluid management lowered risk of starting renal replacement therapy (RRT) and progression to AKI stage 3, and none of the interventions reduced the risk of death in AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early consults with nephrology have shown potential benefit by lowering risk of progression to AKI stage 3 through interventions such as early fluid adjustment. 18 Hospitals may consider implementing an AKI alert system using existing EMR infrastructure to generate automated consultations with the nephrology division, which has shown to be associated with improved rate of recovery from AKI. 19 Ultimately, these findings also suggested that the role of the nephrologist in assisting in the care of children with AKI when RRT is not required, is unclear to other healthcare providers.…”
Section: Discussionmentioning
confidence: 99%